Identification of total coliform and E.Coli bacteria contamination in the refill drinking water depot located in Pringsewu sub-district - Arif, Muhammad; Sandro, Mario; Sahroni, Mizan (Institute Of Computer Science (IOCS), 2024)
The demand for high-quality and safe drinking water has led to an increase in the number of refill drinking water depots. While these depots offer a more affordable option, not all of them can guarantee the safety of their products. Coliforms, which are indicative of fecal contamination, can pose a significant health risk to consumers. This research aims to identify the presence of total coliform and E. Coli bacteria in the refill drinking water depots located in Pringsewu sub-district. The study employed an analytical method with an observational approach to analyze the samples collected from the depots. The results revealed that 3 out of 5 depots (60%) tested positive for total coliform bacteria above the standard, and one sample (20%) did not meet sanitation inspection standards.